The Oxford handbook of translation studies / Kirsten Malmkjær, Kevin Windle - Malmkjær, Kirsten
This book covers the history of the theory and practice of translation from Cicero to the digital age. It examines all major processes of translation, offers critical accounts of current research, and compares competing theoretical perspectives. It considers all kinds of translation from sacred texts, poetry, fiction, and sign language to remote, consecutive, and simultaneous interpretation in legal, diplomatic, and commercial contexts. The two opening parts of the book consider the history of translation theory and central concepts in the study of translation. Parts III, IV, and V cover the written text, the interpretation of speech and sign language, and the role of translation in mixed-mode and multimedia contexts. Part VI considers the contributions and challenges of information technology including the uses and limitations of machine technology. The final part looks at the teaching and training of translators and interpreters. -- Book jacket.